Acute and Chronic Iron Overloading Differentially Modulates the Expression of Cellular Iron-homeostatic Molecules in Normal Rat Kidney. (November 2018) - Refaat, Bassem; Abdelghany, Abdelghany Hassan; BaSalamah, Mohammad A.; El-Boshy, Mohamed; Ahmad, Jawwad; Idris, Shakir
Little is known about the renal responses to acute iron overloading. This study measured the renal tubular expression of transferrin receptor-1 (TfR1), cubilin/megalin receptors, hepcidin, ferroportin, and ferritin chains following subacute intoxication of 40 male Wistar rats with a single oral dose of ferrous iron (300 mg/kg). The animals were randomly subdivided into 4 equal subgroups at the time of necropsy (1, 2, 4, and 8 hr). The results were compared with the controls ( n =15) and with the chronic group ( n =15), which received iron for 4 weeks (75 mg/kg/day; 5 days/week). Although both toxicity models inhibited TfR1, they upregulated the cubilin/megalin receptors and hepcidin, and triggered iron deposition in tubular cells. The ferritin heavy-chain and ferroportin were downregulated in the 2-hr and 4-hr acute subgroups, whereas chronic toxicity promoted their expression, compared with controls. Moreover, the 4-hr and 8-hr subgroups had higher intracellular Fe +2 and marked cell apoptosis compared with the chronic group. In conclusion, the kidney appears to sustain iron reabsorption in both intoxication models. However, the cellular iron storage and exporter proteins were differentially expressed in both models, and their inhibition post-acute toxicity might contribute toward the intracellular accumulation of Fe +2, oxidative stress, and ferroptosis.